Perancangan UI/UX Sistem Registrasi Pasien Poli Voluntary Conseling anda Testing (VCT) Berbasis Website dengan Metode Design Thinking - Retrisia, Mellysa; Saputri, Nurul Adha Oktarini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
RSUD Dr. Sobirin is one of the health service agencies functioning as a health service unit to help solve problems experienced by patients. The clinic is divided into several parts, one of which is the Voluntary Counseling and Testing (VCT) clinic. Currently, the problem faced by the hospital is the low utilization of VCT poly services due to the low level of public knowledge about HIV and VCT services. This is because people are afraid of the stigma and discrimination of others and the large number of queues that have accumulated resulting in the length of the registration process. Therefore, Dr. Sobirin Hospital needs a registration information system in the field of website-based UI/UX design using Figma software. The UI/UX design will be integrated with SIMRS which is used in the registration of RSUD Dr. Sobirin. Design Thinking is a creative problem solving method that involves users into the thinking process and makes the user's perspective the main consideration of the problem solving process. The stages consist of Empathize, Define, Ideate, Prototype, and Test. This design uses System Usability Scale (SUS) testing. The final result of this research is a website-based prototype design.